Blockchain Technology Adoption for Life Insurance: Risk, Readiness, and Relevance - Susianto, Isyrofi; Yazid, Setiadi; Ermawan, Geri Yesa (International Journal of Advances in Data and Information Systems, 2025)
Blockchain technology has been widely discussed as a transformative solution for operational inefficiencies in the insurance sector, particularly in automating claims processing, enhancing transparency, and ensuring data immutability. However, adoption within the life insurance industry remains limited. This paper investigates the barriers and potential of blockchain implementation in life insurance through a mapping analysis using the People–Process–Technology (PPT) framework into risk, readiness, and relevance. The research identifies strategic misalignment with existing revenue models, regulatory compliance frictions, and organizational readiness gaps as key obstacles. A five-year cost comparison indicates that while blockchain incurs higher initial investment, it delivers lower operational costs in the long run—particularly in high-volume, deterministic insurance products. Architectural comparisons further highlight the operational advantages and integration challenges of blockchain-based systems over traditional IT infrastructures. The study concludes that although blockchain holds significant promise, its adoption depends on targeted use case selection, organizational transformation, and regulatory alignment.